The simplified polynomial after standard form will be;
⇒ - 8x² - 43x - 36
What is an expression?
Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The algebraic expression is;
''The expression (3x + 6)² is subtracted from x² - 7x.''
Now,
We can formulate as;
⇒ (x² - 7x) - (3x + 6)²
⇒ x² - 7x - (9x² + 36x + 36)
⇒ x² - 7x - 9x² - 36x - 36
⇒ - 8x² - 43x - 36
Thus, The simplified polynomial after standard form will be;
⇒ - 8x² - 43x - 36
Learn more about the expression visit:
brainly.com/question/1859113
#SPJ1